2017
DOI: 10.1007/s10570-017-1278-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl accessibility in wood cell walls as affected by drying and re-wetting procedures

Abstract: The first drying of wood cell walls from the native state has sometimes been described as producing irreversible structural changes which reduce the accessibility to water, a phenomenon often referred to as hornification. This study demonstrates that while changes do seem to take place, these are more complex than what has hitherto been described. The accessibility of wood cell wall hydroxyls to deuteration in the form of liquid water was not found to be affected by drying, since vacuum impregnation with liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
3
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 45 publications
8
73
3
4
Order By: Relevance
“…For calculating the relative accessibility of hydroxyls to water, it is implicitly assumed that molar absorptivities of O-H and O-D vibrations are equal. This is not necessarily correct as O-D stretching vibrations in cellulose, starch, and wood have been reported to be about 10% more intense than O-H stretching vibrations (Mann and Marrinan 1956b;Nara et al 1981;Thybring et al 2017). From theoretical calculations, O-D stretching vibrations are expected to be less intense than O-H stretching vibrations (Crawford 1952;Swenson 1965), in line with studies on liquid normal and heavy water showing 29% lower intensity for O-D stretching vibrations (Venyaminov and Prendergast 1997).…”
Section: Vibrational Spectroscopymentioning
confidence: 84%
See 1 more Smart Citation
“…For calculating the relative accessibility of hydroxyls to water, it is implicitly assumed that molar absorptivities of O-H and O-D vibrations are equal. This is not necessarily correct as O-D stretching vibrations in cellulose, starch, and wood have been reported to be about 10% more intense than O-H stretching vibrations (Mann and Marrinan 1956b;Nara et al 1981;Thybring et al 2017). From theoretical calculations, O-D stretching vibrations are expected to be less intense than O-H stretching vibrations (Crawford 1952;Swenson 1965), in line with studies on liquid normal and heavy water showing 29% lower intensity for O-D stretching vibrations (Venyaminov and Prendergast 1997).…”
Section: Vibrational Spectroscopymentioning
confidence: 84%
“…As deuterium ( 2 H) is about 1 g/mol heavier than protium ( 1 H), the material dry mass increases slightly upon deuteration (* 1% for untreated wood), which can only be measured with enough accuracy using very sensitive balances. Therefore, vapourphase deuteration has been used on untreated wood in an early-stage sorption balance (Taniguchi et al 1978) as well as recently on untreated (Thybring et al 2017) and modified wood (Popescu et al 2014;Rautkari et al 2013) using modern automated sorption balances, yielding information about how many hydroxyls are accessible for water. It should be noted, however, that not all accessible hydroxyls will have their hydrogen exchanged.…”
Section: Automated Sorption Balancesmentioning
confidence: 99%
“…Consequently, starting desorption from a high hygroscopic RH reached by absorption, yields scanning isotherms, and the moisture content in the upper part of the hygroscopic range is underestimated if these scanning isotherms are interpreted as actual desorption isotherms. In addition, water-saturation is necessary in order to re-open the cell wall structure in Norway spruce after drying and make all hydrophilic functional groups accessible for water (Thybring et al 2017). Thus, initiating desorption from less than water-saturation might not provide sorption data representative of the actual desorption isotherm at any RH level due to insufficient re-opening of the cell wall structure.…”
Section: Sorption Measurements and Hysteresis Evaluationmentioning
confidence: 99%
“…WRV is a parameter that may be used as a proxi for changes in biomass structure and composition, and may also be used to illustrate hornification of biomass . Weiss et al also suggested that a higher level of WRV is indicative of reduced recalcitrance in pretreated biomass.…”
Section: Resultsmentioning
confidence: 99%
“…WRV is a parameter that may be used as a proxi for changes in biomass structure and composition, and may also be used to illustrate hornification of biomass. 32,33 Weiss et al 23 also suggested that a higher level of WRV is indicative of reduced recalcitrance in pretreated biomass. When drying below fiber saturation, cell wall biopolymers may connect through hydrogen bonding, which results in shrinkage and loss of pores in the cell wall.…”
Section: Water Retention Valuementioning
confidence: 99%